The Relationship Between the COVID-19 Pandemic and Vaccine Hesitancy: A Scoping Review of Literature Until August 2021 - Matilde de Albuquerque Veloso Machado; Bjelle Roberts; Brian Li Han Wong; Brian Li Han Wong; Robin van Kessel; Robin van Kessel; Robin van Kessel; Elias Mossialos; Elias Mossialos (Frontiers Media S.A., 2021)
Background: Vaccines have been contributing to eradicate or drastically reduce the incidence of common diseases. Simultaneously, vaccine hesitancy is considered among the top ten global health threats. The COVID-19 pandemic has caused a tremendous impact on health, economics, and society worldwide, while also reinforcing faulty beliefs about the necessity of vaccine programs as a whole. This study aims to synthesise evidence on the impact of the COVID-19 pandemic on vaccine hesitancy.Methods: A scoping review of literature between 1 January 2020 and 1 August 2021 was performed.Results: COVID-19 vaccine acceptance decreased from more than 70 to <50% in 8 months starting from January 2020. Healthcare professionals demonstrate higher rates of vaccine receptivity than the public, which was more influenced by (social) media. The circulation of misinformation was associated with increased fear of side effects related to COVID-19 vaccines. Regarding other vaccines coverage, parents' intentions to vaccinate their children against influenza increased 15.8% during the COVID-19 pandemic so far. Nonetheless, the number of vaccines administered decreased, influenced by factors like fear of being exposed to the virus at healthcare facilities and restrictions.Conclusions: Several efforts should be undertaken to improve vaccine acceptance and coverage now and beyond the pandemic to optimal population protection.